Pemanfaatan Aplikasi Canva Dalam Membuat Media Pembelajaran - Munasiah Munasiah; Zikriah Zikriah; Heriyati Heriyati (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2023)
Corona has had an impact in various fields. In the field of education, Corona has had an impact, including forcing teachers to be more technologically savvy. Online learning is implemented to reduce the spread of COVID-19. The implementation of online learning has made teachers upgrade themselves by participating in various seminars and training on technologies that are beneficial to the teaching and learning process. From this, the service team held socialization about the Canva application for teachers of SD Negeri Sukamaju Baru 1, which sought to increase teachers' understanding of the Canva application and the use of the Canva application in making learning media. This community service activity uses three stages, namely: 1) the planning stage; 2) the socialization stage. 3) At the evaluation stage of its implementation, the method used is a lecture in the form of a presentation, namely presenting about Canva, and the practical method, namely having activity participants carry out direct practices, including creating an account on the Canva application, then creating a presentation file as a learning medium and making a face-to-face video. This service activity had a positive impact on the teachers of SD Negeri Sukamaju Baru 1, namely that the teachers at the school understood more about the Canva application and started using Canva to make learning media.